A Development of Factor Model of High Digital Competencies for Vocational Students - Arjmungkorn, Anonglak; Chianchana, Chaiwichit; Na Wichian, Sageemas (Ratchaphruek Journal, 2025)
This research aims to study, analyze, and verify the construct validity of a high-performance digital competency model for vocational students. The study employed a mixed-methods approach using an exploratory sequential design. In the qualitative phase, data were collected through a document review of related research, interviews with six experts, a brainstorming session with seven participants, and content analysis. The quantitative phase consisted of two parts: (1) an exploratory factor analysis (EFA) involving a sample of 300 vocational teachers who responded to a structured questionnaire, and (2) a second-order confirmatory factor analysis (CFA) involving a separate sample of 300 vocational students. The findings revealed that 1) Content analysis of the documents and expert interviews initially identified 142 items, which were refined and synthesized into 31 indicators, 2) The EFA results indicated three main components and 19 key indicators with factor loadings of ≥ 0.65. These components are: Digital Application (DC) with 10 indicators, Digital Use for Work (DW) with 5 indicators, and Digital Literacy and Access (DL) with 4 indicators, and 3) The second-order CFA demonstrated a good model fit with the empirical data (Chi-Square = 124.525, df = 101, p = .056, Relative Chi-Square = 1.233, GFI = .959, NFI = .966, TLI = .989, CFI = .993, RMSEA = .028, RMR = .016). The factor loadings for all components were statistically significant: DC = 0.850, DW = 0.972, and DL = 0.890. These results support the validity of the proposed model as a tool for assessing and enhancing digital competencies among vocational students.